"My baby is fine, no need for more clinic visits." Facilitators and barriers for utilisation of follow‐up services for children born preterm in low‐resource setting: Parents' perceptions. Issue 3 (9th February 2023) - Namiiro, Flaviah B.; Nolens, Barbara; Rujumba, Joseph; Kiguli, Sarah; Batte, Anthony; van den Akker, Thomas
Abstract: Objectives: We sought to understand the facilitators and barriers impacting utilisation of follow‐up services for children born preterm as perceived by parents in a low‐resource setting. Methods: We conducted a qualitative study at Mulago Hospital, Uganda, with parents of children born preterm and aged 22–38 months at the time of the study. We collected data using five in‐depth interviews and four focus group discussions. Data were analysed using thematic analysis informed by the social–ecological model. Results: Ten subthemes emerged that could be grouped into three main themes: (1) Individual : parents' knowledge, parenting skills, perception of follow‐up and infant's condition; (2) Relationship : support for the mother and information sharing; (3) Institution : facility setup, cost of care, available personnel and distance from the facility. Parents of preterm infants perceived receiving timely information, better understanding of prematurity and its complications, support from spouses, availability of free services and encouragement from health workers as facilitators for utilisation of follow‐up services. Limited male involvement, parents' negative perception of follow‐up, stable condition of infant, health facility challenges especially congestion at the hospital, distance and care costs were key barriers. Conclusion: An interplay of facilitators and barriers at individual, interpersonal and health system levels encourage or deter parents from taking their preterm children for follow‐up services. Improving utilisation of services will require educating parents on the importance of follow‐up even when children are not sick, eliciting maternal support from spouses and peers and addressing health system gaps that make follow‐up unattractive and costly.